ANALYSIS OF PREPOSITION USAGE IN THE ONLINE NEWS PORTAL DETIK.COM - Gunawan, Inra; Indri andriyani; Silviani; Iis Lisnawati (Media Inovasi Pendidikan dan Publikasi, 2024)
Language has a function as a means of communication. To fulfill this function, language must be understood by both parties who will communicate. This research aims to find out whether the information in the Detik.com online news portal is credible and in accordance with writing rules, especially in writing prepositions. This research uses a qualitative approach, an approach that prioritizes an inductive mindset and is not bound by theory, but rather by facts that arise naturally in the field. The method used is descriptive analytical method, which is a research method used by researchers to describe an object that contains phenomena in order to answer a research problem. The research technique used in this research is observation, which is a research technique carried out by observing the events or events under study. The data source is obtained from the Detik.com online news portal published in November. The results of this study indicate that the writing of prepositions is in accordance with the writing rules so that the news on the Detik.com online news portal can be used as a credible and reliable source of information.